Probiotics in Pediatrics: How to Choose Effective and Safety Specimen for a Child - Vladimir N. Drozdov; Olga A. Vorob'eva; Aleksandr A. Astapovsky; Evgeniya V. Shikh (Вопросы современной педиатрии)
The challenge with selection of probiotic is still very topical due to the huge amount of different kinds of probiotics on pharmaceutical market and due to the lack of major studies about their effects in children. In this regard the administration of such specimens in children should be performed with special selectivity. The efficiency of the most studied probiotic bacterial strains used in prevention and treatment were analysed in this article. Requirements for probiotic microorganisms (included those used in pediatrics) were described. It is noted that probiotics are often considered as food supplement. However they are implemented in prevention and treatment of functional disorders and diseases of the gastrointestinal tract.